SPIRITUAL INTELLIGENCE AND ORGANIZATIONAL COMMITMENTS OF PAC IPNU MAGELANG REGENCY - Kurnia Ulfa; Adi Heryadi (Psikis : Jurnal Psikologi Islami, 2020)
This study was conducted at the branch subsidiary (PAC) IPNU (Nahdhatul Ulama Student Association) in Magelang Regency. The study population was the administrators of Magelang Regency IPNU PAC which consisted of 18 PACs. The sample in this study amounted to 157 people selected by cluster random sampling technique. The topic of research is the extent to which the organizational commitment of the board when linked to spiritual intelligence, because managing a non-profit organization is different when we are managing a profit organization. The scale of spiritual intelligence and the scale of organizational commitment become data collection tools in this study where the second scale was made by researchers. The data collected were analyzed with the product moment correlation technique resulting in a value of 0.556 with a significance level of 0,000 (p <0.01), indicating that spiritual intelligence and organizational commitment of PAC IPNU administrators in Magelang Regency were highly correlated. The effective contribution of the spiritual intelligence variable contributed 30.9% to the organizational commitment of the PAC IPNU Magelang District management, while 69.1% of the organizational commitment was influenced by other factors.